Тенденції розвитку підприємств-постачальників енергоресурсів в умовах лібералізації енергоринку - Шведкий, В.А. (Управління економікою: теорія та практика, 2021)
У статті виявлені тенденції розвитку підприємств-постачальників енергоресурсів, які склалися під впливом лібералізації ринку. Серед них: закріплення дивізіонального принципу розбудови організаційної структури; створення нових клієнтських моделей, покликаних максимально наблизити постачальника до споживача; діджиталізація сервісів; поступове зміщення акцентів на застосування нецінових методів конкуренції. Визначено ризики, що виникають для цієї групи ринкових суб’єктів. The article reveals the trends in the development of energy supply enterprises that have developed under the influence of market liberalization, and identifies the risks that arise for this group of market entities.
It has been proven that the liberalization of the market, although not brought to a logical conclusion, has significantly improved the quality of service in the field of energy supply, stimulated the development of innovative products, the transition to more progressive business processes, especially digital ones. Under the influence of the gradual opening of the market, new trends in the development of the supply sector were formed, the main ones of which are: 1) consolidation of the divisional principle of building the organizational structure (with an orientation in the business segment on the service’s individualization, and in the household segment - on the sales’ individualization; 2) creation of new customer models designed to bring the supplier as close as possible to the consumer and to implement an aggressive offensive strategy as the household segment of the market is finally liberalized; 3) digitalization of services; 4) gradual preparation for the shift of emphasis to the use of non-price methods of competition.
It was argued that the new market configuration dictates the requirements for the organizational and management structures of suppliers and determines the content of new products on the market. At the same time, the new market model generates significant risks, namely: increased asymmetric nature of competition, monopolization, reduced financial stability of suppliers due to non-payment. Most of these risks are systemic in nature, formed in the external environment and cannot be completely eliminated by the efforts of suppliers in the field of service improvement or the introduction of innovative products.